Physical culture as a means of physical activity and strengthening the health of young students - Iryna Sundukova; Oleksii Stasenko; Yaroslavа Lohvinova; Yuliia Kovalova; Olena Radionova (Universidad de Murcia, 2024)
Modern educational systems are aimed at the comprehensive development of young people, and physical education is an integral means of such development. The article aimed to consider the integration of physical culture in these systems, and its individual impact on youth health in terms of medical, educational, and sports industries, as one of the key factors in popularisation, to achieve the most objective overview. The key method in the study of this issue was descriptive, as one that allows full presenting the reviews of various studies on this topic from the perspective of modern scientific views. Methods of synthesis, analysis, abstraction, and analogies - allowed to approach the study of this topic comprehensively and consider one of the most important means of physical health through the prism of the use of theoretical methods of scientific knowledge. Thus, as a result of this work, this study was isolated, structured, formed, and combined into a single descriptive system. Physical culture is described as a means of strengthening the health of students in view of their inclusion in various interrelated areas of socio-economic life. The materials of this article can be useful as additional material for students, teachers, and researchers, to some extent physicians or speechwriters interested in areas: education, health, and physical education as a separate discipline or individual means to improve the quality of life, and also a wide range of interested readers.